Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.29185/hayuretim.363905
|View full text |Cite
|
Sign up to set email alerts
|

Memeli Çiftlik Hayvanlarında Stres, Fizyoloji ve Üretim İlişkileri

Abstract: ÖzetFarklı üretim sistemlerinde yetiştirilen hayvan türleri farklı çevresel stres faktörlerine maruz kalmakta ve bunlarla fizyolojik ve davranışsal tepkiler yoluyla mücadele etmektedirler. Bu mücadelelerin başarısız olması, hayvanların refah durumlarını açık olarak tehdit etmekle birlikte üretim etkinlik ve kalitelerini de olumsuz yönde etkilemektedir. Stres esnasında stres hormonlarının (HPA ve SA aksı hormonları) ve sitokinlerin üretiminde artışlar gerçekleşirken, anabolik hormonların (IGF-I, GH, tiroit horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(20 reference statements)
0
5
0
1
Order By: Relevance
“…The dairy cows respond to stress in two stages (acute and chronic). Acute and chronic stress are controlled by the 'Sympathetic-Adrenal-Medullary (SAM)' and 'Hypothalamus-Pituitary-Adrenal (HPA) axis', respectively (Pehlivan and Dellal, 2014;Bagath et al, 2019). The acute stress responses are short-term (from a few minutes to a few days), and cattle can adapt with short-term physiological adaptation events such as drinking more water, increasing respiration and sweating to reduce the heat load on the body (Idris et al, 2021).…”
Section: Physiological Thermal Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The dairy cows respond to stress in two stages (acute and chronic). Acute and chronic stress are controlled by the 'Sympathetic-Adrenal-Medullary (SAM)' and 'Hypothalamus-Pituitary-Adrenal (HPA) axis', respectively (Pehlivan and Dellal, 2014;Bagath et al, 2019). The acute stress responses are short-term (from a few minutes to a few days), and cattle can adapt with short-term physiological adaptation events such as drinking more water, increasing respiration and sweating to reduce the heat load on the body (Idris et al, 2021).…”
Section: Physiological Thermal Regulationmentioning
confidence: 99%
“…This process activates or initiates a series of physiological response in order to create the necessary reaction against stress by using the reserves of body and to provide physical balance (Altınçekiç and Koyuncu, 2012). This set of physiological responses results in elevation of the pulse, blood pressure, respiratory rate, and blood sugar, as well as suppression of certain anabolic events (digestion, reproduction, growth and immune system) (Farooq et al, 2010;Pehlivan and Dellal, 2014;Niyas et al, 2015). When short-term adaptation pathways fail as a result of prolonged environmental stress, body temperature significantly increases.…”
Section: Physiological Thermal Regulationmentioning
confidence: 99%
“…Kalp atış hızının düşürülmesi ve sindirim gibi fizyolojik olayların gerçekleştirilmesi için gerekli olan rahatlama devresinde parasempatik iz yolu görev yapar. Tehlike durumlarında ise sempatik iz yolu devreye girer ve adrenalin hormonunun adrenal bezden salgılanmasını uyarır (Pehlivan and Dellal, 2014). Aynı zamanda Turuncus Ensephali'nin Locus Coeruleus bölgesinde bulunan sinir lifleri de stres faktörleri tarafından uyarıldıklarında noradrenalin hormonu salgılamaktadırlar (Squires, 2010).…”
Section: Stres Oluşum Mekanizmasıunclassified
“…In the mean time, it has been observed that the number of heart beats is higher during eating than standing [13][14][15][16]. It is even known that milk yield is affected by stress experienced by animals during feeding [13][14][15][16][17][18]. Residual feed is another problem in animal farms.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, stress negatively affects the lactation period. It negatively affects milk production by causing a decrease in oxytocin hormone production during stress [18,[23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%